Financiamento da educação superior: um print da internacionalização no Instituto Federal da Paraíba (2010-2019) - Moura, Helena Lima de (2023)
The internationalization of higher education emerges as the fourth essential dimension of the university, complementing the traditional tripod of teaching, research, and extension, and becoming a crucial parameter for the evaluation indicators of higher education. In that regard, it becomes imperative to direct our focus to this theme, especially in the current context of a globalized and competitive world, increasingly technological and fast-paced. From this perspective, the objective of this research is to offer a situational overview on the financing of the internationalization of higher education at the Federal Institute of Paraíba during the period from 2010 to 2019. To this end, brief considerations will be made about the Internationalization of Higher Education in Brazil, including characteristics of its financing. Regarding the methodology used, a documentary approach of qualitative nature was chosen. After the data analysis, it was verified that there is an internationalization policy with a concentration of actions executed by ARINTER. However, it was not possible to measure the financial values invested in a quantitative way, nor to find transparency of these in the management reports. Therefore, there is a deadlock in accurately determining the percentage of the budget allocated to education internationalization actions at IFPB. In view of this scenario, a DORP – Procedure Guiding Document - was elaborated as a result of this research, containing suggestions for the implementation of strategies that aim to strengthen the governance processes and transparency of budgetary data related to the internationalization of higher education at IFPB. In this way, IFPB ratifies its purpose of providing quality education that considers market, cultural and knowledge challenges through the internationalization of education.